KONSELING KELOMPOK DENGAN PENDEKATAN ANALISIS TRANSAKSIONAL UNTUK MENGATASI AGRESIVITAS - Ulandari Juwita; Yeni Karneli; Netrawati (CV Putra Publisher, 2023)
This study aims to analyze Group Counseling with a Transactional Analysis approach to overcome aggressiveness. The type of research used is literature study, namely research that uses various literature or various library information as research objects. Transactional analysis is an approach in counseling that can be used as a treatment in group counseling. Transactional is a communication relationship between a person and another person, so this approach is more widely applied in a group atmosphere which is an atmosphere where there is a relationship with other people. The form and method of communication will reflect whether there are problems experienced. Aggressiveness is a tendency or urge to harm others by various forms of action.